Pengujian Tarik Pada Baja Karbon Sedang Di Las Smaw Dengan Pemanasan Suhu 900oc Di Quenching Air Kelapa Dan Udara - Erizal Erizal (MAJALAH TEKNIK SIMES, 2021)
From the result of tensile test research on carbon steel plate. After the welding process and treated with a load of 3000 kg get the average calculation value are non treatment ?y = 54,32 kgf/mm², ?u = 28,36 kgf/mm² and ?f = 23,78 kgf/mm². The average value of the tensile test on air quenching are ?y = 29,63 kgf/mm², ?u = 34,93 kgf/mm², ?f = 33,01 kgf/mm². The average value of the tensile test on coconut water quenching are ?y = 22,66 kgf/mm², ?u = 29,47 kgf/mm², ?f = 26,79 kgf/mm². this tensile test research, it can be concluded that coconut water quenching , has better result than air quenching.